2014
DOI: 10.1002/adsc.201400681
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cyclization and Azidation of γ,δ‐Unsaturated Ketone O‐Benzoyl Oximes

Abstract: An intramolecular imination/azidation sequence has been realized through the tetrak-hexafluorophophate [Cu(CH 3 CN) 4 PF 6 ]-catalyzed reaction of g,d-unsaturated ketone O-benzoyl oximes with trimethylsilyl azide (TMSN 3 ). The reaction proceeds via the copper-mediated N À O cleavage and subsequent C À N forming 5-exo cyclization. The thus formed intermediate is then azidated to afford the corresponding dihydropyrrole product. Preliminary mechanistic investigations suggest that the cyclization step does not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In 2014 Yu and co‐workers reported an intramolecular imination/azidation sequence based on γ,δ‐unsaturated keto‐ o ‐benzoyl oximes (Scheme ) . The catalyst used in this case was CuPF 6 , together with a β‐keto ester ligand.…”
Section: Base‐metal‐catalysed Azidation Reactionsmentioning
confidence: 99%
“…In 2014 Yu and co‐workers reported an intramolecular imination/azidation sequence based on γ,δ‐unsaturated keto‐ o ‐benzoyl oximes (Scheme ) . The catalyst used in this case was CuPF 6 , together with a β‐keto ester ligand.…”
Section: Base‐metal‐catalysed Azidation Reactionsmentioning
confidence: 99%
“…In 1999, Narasaka et al reported a palladium-catalyzed intramolecular amino-Heck reaction involving oxidative addition of oxime esters to palladium(0) species as a landmark study. Many transformation reactions using this concept have since been reported. , Recently, a few distinguished mechanistic studies have reported that the involvement of the oxidative addition of oxime esters to palladium(0) was confirmed by the isolation of oxidative adducts. , Although other transition metals such as rhodium, copper, nickel, ruthenium, and iridium have also been studied in terms of their use as a catalyst in similar reactions, there have been no reports on the isolation of the intermediate complexes of these transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction afforded the corresponding azide containing dihydropyrrole 118 in moderate to good yields (Scheme 30). 140 Mechanistically, this reaction proceeds via either the initial formation of iminyl radicals and its rapid 5-exo cyclization followed by Cumediated azidation of carbon radicals (path a) or the oxidative addition of Cu(I) into N−O bond and subsequent 5-exo cyclization and azidation sequence (path b).…”
Section: Rearomatization Along With the Extrusion Of Somentioning
confidence: 99%